Of Manuscript Culture in Early Modern Dubrovnik - Plejić Poje, Lahorka (Poznańskie Studia Slawistyczne, 2018)
In the article’s introduction, the author points to the history of the book as one of the younger sub-disciplines and to its relevance for literary history. This fact is particularly important for old Dubrovnik where the first printing house was opened only in 1783. In the middle part of the article, certain aspects of manuscript culture in early modern Dubrovnik are studied. The author explains why until the 19th century a large part of the Ragusan literature was circulated in manuscripts and what the advantages of the manuscript compared to the printed book are. The author reminds that manuscripts carried out the function of printed books and indicates that printed books were frequently copied by hand.